2023
DOI: 10.3390/cancers15164086
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Microbiome-Derived SCFAs in Prostate Cancer: Analyzing Gut Microbiota, Racial Disparities, and Epigenetic Mechanisms

Abstract: Prostate cancer (PCa) continues to be the most diagnosed cancer and the second primary cause of fatalities in men globally. There is an abundance of scientific evidence suggesting that the human microbiome, together with its metabolites, plays a crucial role in carcinogenesis and has a significant impact on the efficacy of anticancer interventions in solid and hematological cancers. These anticancer interventions include chemotherapy, immune checkpoint inhibitors, and targeted therapies. Furthermore, the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 161 publications
0
2
0
Order By: Relevance
“…Although the urinary microbiota in prostate cancer pathogenesis is still being actively researched, its contribution to our understanding of how bacterial communities interact with this relatively common malignancy can be quite revealing (33).…”
Section: Role Of Urinary Microbiota In Prostate Cancer Pathogenesismentioning
confidence: 99%
“…Although the urinary microbiota in prostate cancer pathogenesis is still being actively researched, its contribution to our understanding of how bacterial communities interact with this relatively common malignancy can be quite revealing (33).…”
Section: Role Of Urinary Microbiota In Prostate Cancer Pathogenesismentioning
confidence: 99%
“…Diet and physical activity also play important roles in the development and progression of PCa, particularly in relation to ethnicity, at different incidence rates 105 . Additionally, an increasing body of research over the past decade has demonstrated the significant role that the gut microbiota plays in the occurrence and development of PCa 106 , 107 . Liss et al conducted an analysis of the gut microbiota in 133 U.S. men who underwent prostate biopsy; they performed 16S rRNA amplicon sequencing on 105 samples (64 with cancer and 41 without cancer) 108 .…”
Section: Is the Gut Microbiota Implicated In Tumorigenesis?mentioning
confidence: 99%